Phase-dependent strategy to mimic quantum phase transitions - Zhou, Yuan; Cao, Lian-Zhen; Wang, Qing-Lan; Hu, Chang-Sheng; Zhang, Zhu-Cheng; Xiong, Wei (Frontiers in Quantum Science and Technology, 2023)
A hybrid quantum system of an ensemble of collective spins coupled to a surface acoustic wave (SAW) cavity through a sideband design is proposed in this work. Assisted by a dichromatic optical drive with a phase-dependent control, this spin ensemble can effectively mimic different types of long-range Lipkin-Meshkov-Glick (LMG) interactions, and then undergoes the quantum phase transitions (QPTs) because of the phase-induced spontaneous symmetry breaking (SSB). In addition, this phase-controlled scheme can also ensure the dynamical preparation of spin squeezed state (SSS), which potentially supplies a useful application in the area of quantum measurement. This investigation may be considered as a fresh attempt on quantum manipulation by using the acoustic control, and it can also provide a promising route towards some useful applications for quantum information processing, especially, the adiabatic preparation of multiparticle entangled ground states via QPTs, i.e., the Greenberger-Horne-Zeilinger (GHZ) state or W-type state.